2022
DOI: 10.3390/microorganisms10050846
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Chromosome Structural Dynamics and Gene Expression—A Chicken and Egg Dilemma?

Abstract: Prokaryotic transcription was extensively studied over the last half-century. A great deal of data has been accumulated regarding the control of gene expression by transcription factors regulating their target genes by binding at specific DNA sites. However, there is a significant gap between the mechanistic description of transcriptional control obtained from in vitro biochemical studies and the complexity of transcriptional regulation in the context of the living cell. Indeed, recent studies provide ample ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 136 publications
1
10
0
Order By: Relevance
“…The result that chromatin interaction between genes with regulation relationship is stronger than that of the genomic overall is in line with our previous finding that chromatin interaction within biological pathways is not random [14] and supports the connection between 3D genome organization and gene regulation [33]. It was found that positive regulation requires a larger but negative regulation requires a smaller spatial distance compared with the TRN, which indicates different regulation types have different requirements on the spatial arrangement of genes in 3D space to better fulfill their functions.…”
Section: Discussionsupporting
confidence: 91%
“…The result that chromatin interaction between genes with regulation relationship is stronger than that of the genomic overall is in line with our previous finding that chromatin interaction within biological pathways is not random [14] and supports the connection between 3D genome organization and gene regulation [33]. It was found that positive regulation requires a larger but negative regulation requires a smaller spatial distance compared with the TRN, which indicates different regulation types have different requirements on the spatial arrangement of genes in 3D space to better fulfill their functions.…”
Section: Discussionsupporting
confidence: 91%
“…It has been documented that bacteria can fix their genome to perform better in the environment where they live, be it natural or laboratory ( Nagy-Staron et al, 2021 ; Saleski et al, 2021 ). It has been proposed that genes in the genome have different levels of expression depending on their location and their syntenic organization, which in many bacteria has allowed the correlation of gene clusters with the virulence abilities of pathogenic bacteria ( Le Berre et al, 2022 ). One of the outstanding aspects at the moment in the genetics of bacteria is the presence of islands of pathogenicity ( Desvaux et al, 2020 ), which are short segments of the genetic material that concentrate genes that encode virulence factors ( Wu, 2015 ), antibiotic resistance functions ( Debroas and Siguret, 2019 ; Ellabaan et al, 2021 ; Maciel-Guerra et al, 2022 ), proteins that ensure DNA perpetuation, and enzymes involved in the internal mobility of DNA ( Hallstrom and McCormick, 2015 ; Smyshlyaev et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This transformation of supercoil energy into genetic information is enabled by the specific coupling of the DNA thermodynamic stability (essentially, DNA structural dynamics) with genetic function [ 12 , 104 , 107 ], revealing crosstalk between two different types of information interwoven in the genomic DNA sequence. Here, we propose that this double informational content of DNA, reflected partly in the interdependence of genomic expression and structural dynamics of the chromosome [ 3 , 15 , 120 , 179 ], enables perpetual monitoring of the physiological state, manifested in the changing genomic binding patterns of NAPs and RNAP sigma factors during the bacterial growth cycle [ 6 , 34 , 35 , 118 , 180 ]. By coupling the temporally changing ion composition, intracellular pH, and energy levels via DNA topology to the spatially shifting gene expression pattern in the genome (note that during the growth cycle the gene expression changes as a function of distance from OriC; Figure 3 C), the bacterial population grown in batch culture could also measure the ‘traveled distance’ (i.e., its age) along the growth cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, on the transition to the stationary phase associated with the global relaxation of the DNA, the relatively A/T-rich Ter pole is activated, whereas the OriC pole is repressed. Since it is assumed, as mentioned above, that the chromosome configuration and genomic transcription are interdependent [ 6 , 15 , 16 , 119 , 120 ], the successive activation of OriC and Ter poles likely reflects the coordinately changing configuration and genetic activity of the chromosome, which is associated with the global redistribution of RNAP in the nucleoid [ 118 , 121 ]. In this regard, the non-random distribution of the binding sites of the NAPs and especially of the DNA gyrase and major RNAP sigma factors along the OriC-Ter axis that were observed in the E. coli genome [ 6 , 14 ], are suggestive.…”
Section: Role For Changing Chromosome Configuration In Organizing Gen...mentioning
confidence: 99%